Kitāb-i Īrānī : Chahār maqāla dar mabāḥith-i matn pizhūhī, nuskha shināsi wa kitāb ārāʾī - Richard, Francis (Miras Maktoob, ISBN: 9789004365452., 2019)
For many years, Francis Richard (1948) was responsible for the Persian manuscripts in the Oriental collection of the Bibliothèque Nationale de France. The author of numerous publications on Persian manuscripts and their tradition and much esteemed among his peers in Iran, this is the Persian translation of Richard's Le livre persan (BnF, 2003), containing the following essays: "Le Supplément persan : l'acquisition de manuscrits par le département des Manuscrits de 1739 à nos jours", "La transmission des textes dans le monde iranien : quelques pratiques liées à la culture manuscrite", "Un cas de « succès littéraire » : la diffusion des œuvres poétiques de Djâmî de Hérât à travers tout le Proche-Orient", and "Le sarlowh ou frontispice enluminé : un décor fréquent dans les manuscrits persans." In recognition of his great services to Persian studies, part one of a two-volume Persian liber amicorum was published in Tehran in 2005.